Fascism as Dehumanization: Alexander Moritz Frey's Political Fables. (2nd January 2017) - Mayer, Paola; Mueller, Ruediger
Abstract : This article explores Alexander Moritz Frey's use of topoi from the fable genre to satirize the political right during the Weimar Republic, particularly in its most extreme form, National Socialism. It focuses on four short narrative texts, two of them still unpublished, which attack militarism, expansionist politics, and the Nazi doctrines of racial purity and eugenics. We argue that Frey adapts the fable's techniques of defamiliarization, reductio ad absurdum, and especially its conflation of the animal and the human, to expose what he regarded as the most pernicious effect of fascism: its degradation of the human to brute beast, domestic animal, even inanimate tool.